2012
DOI: 10.1071/rd11180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tubal explants and their secretions on bovine spermatozoa: modulation of ROS production and DNA damage

Abstract: Although low levels of reactive oxygen species (ROS) play a physiological role in maintaining sperm function, an increase in ROS generation above these levels may result in the induction of sperm membrane and DNA damage. The main objective of this study was to determine whether bovine oviducal explants (TU) and their conditioned media (CM) have a modulatory effect on the production of ROS, and consequently, on sperm DNA integrity. Thawed sperm were exposed to bovine TU and to CM obtained from the ampullar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In cows, GPx3 [ 52 ] and GPx4 [ 53 ] were under-expressed in the ampulla and over-expressed in the isthmus. This is because the ampulla is the site of fertilization, and spermatozoa need ROS presence for the capacitation to occur, while spermatozoa in the isthmus need to be protected against ROS-induced damage as they constitute a sperm reservoir [ 54 ]. High GPxs activity was also detected in cow oviductal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In cows, GPx3 [ 52 ] and GPx4 [ 53 ] were under-expressed in the ampulla and over-expressed in the isthmus. This is because the ampulla is the site of fertilization, and spermatozoa need ROS presence for the capacitation to occur, while spermatozoa in the isthmus need to be protected against ROS-induced damage as they constitute a sperm reservoir [ 54 ]. High GPxs activity was also detected in cow oviductal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antioxidant activity in the oviduct environment has been correlated to spermatic and oocyte protection against ROS damage in the female reproductive tract (Lapointe & Bilodeau, ). According to Gómez, Alvarez, Risopatrón, Romero, and Sánchez (), low levels of ROS play a key role in sperm function; however, an increase in ROS generation above these levels may result in the induction of sperm membrane and DNA damage. Georgiou et al () identified secretory proteins from the oviduct, such as SOD, glutathione reductase and thioredoxin families (all identified in the protein network analysis in this study) as the main components of mammalian enzymatic redox pathways that control extracellular ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study by Gómez et al. () implies that significant oxidative stress may take place in the oviduct, particularly during short‐term incubation, and this may be related to changes in the antioxidant factors present in the oviducal cells and associated secretions.…”
Section: Fluorescent Detection Of Sperm Function – ‘Known Knowns Unkmentioning
confidence: 99%